Lead wire for non-aqueous electrolyte battery, and non-aqueous electrolyte battery
By adding chromium hydroxide trivalent chromium compound and metal elements to the conductor coating of the extreme ear leads, and using maleic anhydride modified polypropylene resin components in the insulating film, the problems of moisture permeability and conductor corrosion of the lead wire of the nonaqueous electrolyte battery are solved, and higher tolerance and bonding strength are achieved.
Patent Information
- Application Number
- CN202280099506.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-09
- Publication Date
- 2025-04-08
AI Technical Summary
After long-term use of the pole lead of the nonaqueous electrolyte battery, moisture easily passes through the sealing part, causing corrosion between the nonaqueous electrolyte and the metal conductor inside the packaging container, thereby causing the interface between the conductor and the insulating film to peel off.
A conductor coating is used, which contains the trivalent chromium compound and metal element of chromium hydroxide, and the ratio of chromium hydroxide to the trivalent chromium compound is controlled at the most surface. The insulating film consists of a multi-layer structure, including a resin component mainly composed of maleic anhydride modified polypropylene, with an acid modification rate ranging from 0.02% to 0.50%.
Effectively suppress the interface peeling between the conductor and the insulating film, improve the resistance to the non-aqueous electrolyte, enhance the bonding strength between the conductor and the insulating film, and extend the service life of the lead.
Smart Images

Figure CN119790542A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a lead for a nonaqueous electrolyte battery and a nonaqueous electrolyte battery. Background Art
[0002] As electronic devices are miniaturized and lightweight, the electrical components such as batteries and capacitors used in these devices are also required to be miniaturized and lightweight. Therefore, for example, a non-aqueous electrolyte battery is used, which uses a bag as a packaging container and seals a non-aqueous electrolyte, a positive electrode and a negative electrode therein. As the non-aqueous electrolyte, an electrolyte obtained by dissolving a fluorine-containing lithium salt such as LiPF6 and LiBF4 in propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. is used.
[0003] The packaging container is required to have the property of preventing electrolyte or gas from permeating and water from the outside from entering. Therefore, a laminated film obtained by coating a metal layer such as aluminum foil with a resin is used as the material of the packaging container, and the ends of two laminated films are heat-fused to form the packaging container.
[0004] One end of the packaging container is used as an opening, and a non-aqueous electrolyte, a positive electrode plate, a negative electrode plate, a separator, etc. are sealed inside. Furthermore, a lead conductor having one end connected to the positive electrode plate and the negative electrode plate is arranged so as to extend from the inside to the outside of the packaging container, and finally the opening of the packaging container is closed by heat-sealing (thermal welding), and the packaging container and the lead conductor are bonded together to seal the opening.
[0005] The portion of the lead conductor corresponding to the sealing portion is covered with an insulating film, and a material having the insulating film and the lead conductor is called a lead for a non-aqueous electrolyte battery (tab lead). The packaging container and the lead conductor are bonded (thermally welded) via the insulating film. Therefore, the insulating film is required to have such a property that the lead conductor and the packaging container can be kept in adhesion without causing a short circuit between the metal layer of the packaging container and the lead conductor.
[0006] As the above-mentioned tab lead, as a prior art, for example, a non-aqueous electrolyte battery having the following lead has been proposed: the conductor of the positive electrode connection lead and the conductor of the negative electrode connection lead are made of different metals, and the insulation of the lead is provided with an insulating layer that does not melt at the heat sealing temperature of the packaging bag (see Patent Document 1).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 9-265974 Summary of the invention
[0010] The lead wire for a non-aqueous electrolyte battery disclosed herein comprises: a conductor; and an insulating film, the insulating film having one or more layers and covering at least a portion of the outer peripheral surface of the conductor, the conductor having a conductor coating covering at least a portion of the surface, the conductor coating containing a trivalent chromium compound including chromium hydroxide and a metal element, and at the outermost surface of the conductor coating, the mass per unit area of chromium contained in the chromium hydroxide [mg / m 2 ] relative to the mass per unit area of chromium contained in the above trivalent chromium compound [mg / m 2 ] is greater than 0.30 and less than 0.90, the above-mentioned insulating film has an innermost layer, which is stacked on the surface of the above-mentioned conductor coating, and the above-mentioned innermost layer has a resin component containing maleic anhydride modified polypropylene as a main component, and the acid modification rate of the above-mentioned resin component is greater than 0.02 mass% and less than 0.50 mass%. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] [ Figure 1 ] Figure 1 This is a perspective view of a lead for a non-aqueous electrolyte battery according to one embodiment of the present disclosure.
[0012] [ Figure 2 ] Figure 2 This is a partial cross-sectional view of a lead for a non-aqueous electrolyte battery according to one embodiment of the present disclosure.
[0013] [ Figure 3 ] Figure 3 This is a perspective view showing an example of a non-aqueous electrolyte battery including a lead for a non-aqueous electrolyte battery according to an embodiment of the present disclosure.
[0014] [ Figure 4 ] Figure 4 yes Figure 3 A longitudinal cross-sectional view of a non-aqueous electrolyte battery. DETAILED DESCRIPTION
[0015] [Problems to be Solved by the Present Disclosure]
[0016] Even if the tab lead has sufficient adhesion immediately after the opening of the package container is sealed, moisture can easily penetrate from the sealed portion due to long-term use. The permeated moisture reacts with the non-aqueous electrolyte sealed inside the package container to generate hydrofluoric acid. Hydrofluoric acid easily corrodes the metal lead conductor, and due to the corrosion of the metal lead conductor, peeling may occur at the interface between the conductor and the insulating film. Therefore, the tab lead is required to have improved tolerance to the non-aqueous electrolyte.
[0017] An object of the present disclosure is to provide a lead for a non-aqueous electrolyte battery having excellent resistance to a non-aqueous electrolyte of the non-aqueous electrolyte battery.
[0018] [Effects of the present disclosure]
[0019] According to the present disclosure, it is possible to provide a non-aqueous electrolyte battery lead having excellent resistance to a non-aqueous electrolyte of the non-aqueous electrolyte battery.
[0020] [Description of Embodiments of the Present Disclosure]
[0021] First, embodiments of the present disclosure will be listed and described.
[0022] The lead wire for a non-aqueous electrolyte battery disclosed herein comprises: a conductor; and an insulating film, the insulating film having one or more layers and covering at least a portion of the outer peripheral surface of the conductor, the conductor having a conductor coating covering at least a portion of the surface, the conductor coating containing a trivalent chromium compound including chromium hydroxide and a metal element, and at the outermost surface of the conductor coating, the mass per unit area of chromium contained in the chromium hydroxide [mg / m 2 ] relative to the mass per unit area of chromium contained in the above trivalent chromium compound [mg / m 2 ] is greater than 0.30 and less than 0.90, the above-mentioned insulating film has an innermost layer, which is stacked on the surface of the above-mentioned conductor coating, and the above-mentioned innermost layer has a resin component containing maleic anhydride modified polypropylene as a main component, and the acid modification rate of the above-mentioned resin component is greater than 0.02 mass% and less than 0.50 mass%.
[0023] In the lead for a non-aqueous electrolyte battery, the conductor is covered with a conductor coating containing a trivalent chromium compound including chromium hydroxide and a metal element, so that peeling at the interface between the conductor and the insulating film, which is caused by corrosion of the conductor caused by hydrofluoric acid generated by the hydrolysis of the non-aqueous electrolyte, can be suppressed. In addition, the innermost layer stacked on the surface of the conductor coating has a resin component containing maleic anhydride-modified polypropylene as a main component, and the acid modification rate of the resin component is 0.02 mass % or more and 0.50 mass % or less, so that the adhesion between the innermost layer and the conductor coating is good.
[0024] Furthermore, by making the mass of chromium atoms per unit area of the chromium hydroxide in the outermost surface of the conductor film [mg / m 2 ] The mass of chromium atoms per unit area of the trivalent chromium compound [mg / m 2] is 0.30 to 0.90, the conductor coating has a sufficient amount of hydrogen bonds with the maleic anhydride-modified polypropylene in the innermost layer, and the mechanical strength of the conductor coating becomes good, so the bonding strength between the conductor and the insulating film can be improved. On the other hand, at the outermost surface of the conductor coating, the ratio of the mass of chromium atoms per unit area of the chromium hydroxide to the mass of chromium atoms per unit area of the trivalent chromium compound is 0.30 to 0.90, so the amount of hydroxyl groups on the surface is reduced compared with the untreated conductor surface, wherein the untreated conductor surface is believed to be covered with approximately 100% of hydroxide due to the adhesion of moisture from the atmosphere. In contrast, by setting the acid modification rate of the resin component as the main component of the innermost layer to 0.02 mass % to 0.50 mass %, the hydroxyl groups on the conductor surface can be supplemented, so the bonding strength between the conductor and the insulating film can be further improved.
[0025] Therefore, the lead for a non-aqueous electrolyte battery has excellent resistance to the non-aqueous electrolyte of the non-aqueous electrolyte battery.
[0026] The mass of chromium atoms per unit area of the chromium hydroxide relative to the trivalent chromium compound [mg / m 2 ] ratio can be calculated based on the mass of chromium atoms per unit area on the outermost surface of the conductor film and the mass of hydroxyl groups per unit area on the outermost surface of the conductor film. The mass of chromium atoms per unit area on the outermost surface of the conductor film is calculated using X-ray Photoelectron Spectroscopy (hereinafter also referred to as "XPS").
[0027] The “outermost surface of the conductor coating” refers to a region up to a detection depth that can be measured on any surface using the X-ray photoelectron spectroscopy method, and specifically refers to a region down to about 5 nm in the depth direction from any surface.
[0028] In addition, in the present disclosure, the main component refers to a component whose content exceeds 50% by mass.
[0029] The metal element is preferably nickel, aluminum, copper or a combination thereof. When the conductor coating contains nickel, aluminum, copper or a combination thereof as a metal element, the conductivity of the conductor can be further improved.
[0030] The conductor coating preferably further contains a calcium compound, a fluorine compound, or a combination thereof. When the conductor coating further contains a calcium compound, when the lead for a non-aqueous electrolyte battery is used in a non-aqueous electrolyte battery, the stability of the conductor coating to decomposition products of the non-aqueous electrolyte component in the non-aqueous electrolyte battery is improved, thereby having excellent corrosion resistance. When the conductor coating further contains a fluorine compound, the formation of a stable passivation coating can be promoted, thereby further improving the corrosion resistance.
[0031] The acid modification rate of the resin component is preferably 0.10 mass % to 0.50 mass %. When the acid modification rate of the resin component is 0.10 mass % to 0.50 mass %, the bonding strength between the conductor and the insulating film can be further increased.
[0032] The conductor coating preferably has an average thickness of 1 nm to 50 nm. When the average thickness of the conductor coating is 1 nm to 50 nm, the conductor has good corrosion resistance.
[0033] The average thickness of the insulating film is preferably 0.05 mm to 0.50 mm. By setting the average thickness of the insulating film to 0.05 mm to 0.50 mm, the gap between the insulating film and the packaging container can be fully filled, and the amount of water that penetrates from the atmosphere through the insulating film and enters the non-aqueous electrolyte battery can be reduced.
[0034] The average thickness of the innermost layer is preferably 0.01 mm to 0.25 mm. By setting the average thickness of the innermost layer to 0.01 mm to 0.25 mm, the adhesion to the conductor can be improved and the amount of water that penetrates the insulating film from the atmosphere into the non-aqueous electrolyte battery can be suppressed.
[0035] The conductor is preferably nickel, nickel-plated metal, nickel-phosphorus alloy metal, aluminum or aluminum alloy. By making the conductor nickel, nickel-plated metal, nickel-phosphorus alloy metal, aluminum or aluminum alloy, the conductivity and potential resistance can be improved.
[0036] The nonaqueous electrolyte battery of the present disclosure includes an outer container, a plurality of leads for the nonaqueous electrolyte battery arranged to extend from the inside to the outside of the outer container, and a nonaqueous electrolyte.
[0037] By providing the nonaqueous electrolyte battery with a plurality of the nonaqueous electrolyte battery leads, it is possible to suppress separation of the conductor and the insulating film, thereby improving sealing properties.
[0038] [Details of the embodiments of the present disclosure]
[0039] Hereinafter, the nonaqueous electrolyte battery lead and the nonaqueous electrolyte battery according to the present disclosure will be described in detail.
[0040] <Lead for non-aqueous electrolyte batteries>
[0041] Figure 1 This is a perspective view of a lead for a non-aqueous electrolyte battery according to one embodiment of the present disclosure. Figure 2 FIG. 1 is a partial cross-sectional view of a lead wire for a non-aqueous electrolyte battery according to an embodiment of the present disclosure. Figure 1 and Figure 2 As shown, the lead wire 1 for a non-aqueous electrolyte battery includes: a conductor 3; and an insulating film 5 having one or more layers and covering at least a portion of the outer peripheral surface of the conductor 3. In addition, the conductor 3 having one end 4a and the other end 4b has a conductor coating 9 covering at least a portion of the surface. In this embodiment, the insulating film 5 includes: an innermost layer 6 laminated on the surface of the conductor 3, a first insulating layer 8 laminated on the outermost surface of the insulating film 5, and a second insulating layer 7 laminated on the inner surface of the first insulating layer 8. It should be noted that the conductor is equivalent to the lead conductor.
[0042] (conductor)
[0043] The conductor 3 is connected to the electrode of the non-aqueous electrolyte battery. As the material of the conductor 3, from the point of view of conductivity, for example, metal materials such as aluminum, titanium, nickel, copper, aluminum alloy, titanium alloy, nickel alloy, copper alloy, or nickel-plated metal, nickel-phosphorus alloy metal, etc., which are plated with nickel, can be listed. Among these, nickel, nickel-plated metal, and nickel-phosphorus alloy metal are preferably used as the forming material of the conductor 3 connected to the negative electrode of the non-aqueous electrolyte battery. On the other hand, aluminum and aluminum alloy are preferably used as the forming material of the conductor 3 connected to the positive electrode from the point of view of potential resistance, conductivity, and cost.
[0044] The lower limit of the average thickness of the conductor 3 is preferably 0.10 mm. When the average thickness of the conductor 3 is 0.10 mm or more, a sufficient amount of current can flow in practical use as a battery. In addition, the lower limit of the average thickness of the conductor 3 can be further 0.15 mm or 0.20 mm. On the other hand, the upper limit of the average thickness of the conductor 3 is not particularly limited, and can be appropriately set according to the capacity of the non-aqueous electrolyte battery, for example. For example, as the upper limit of the above-mentioned average thickness, 5.00 mm is preferred. When the average thickness of the conductor 3 is less than 5.00 mm, even if the lead is quickly charged and discharged, the resistance heating of the lead part can be suppressed. In addition, the upper limit of the average thickness of the conductor 3 can be further 4 mm. It should be noted that the "average thickness" of the conductor 3 refers to the average value of the thickness measurement values at 10 points. Hereinafter, "average thickness" is defined in the same way.
[0045] (Conductor coating)
[0046] The conductor coating 9 covers at least a portion of the surface of the conductor 3. The conductor coating 9 contains a trivalent chromium compound including chromium hydroxide and a metal element. When the conductor 3 is covered with the conductor coating containing the trivalent chromium compound including chromium hydroxide and a metal element, the corrosion resistance of the conductor 3 becomes good.
[0047] As the metal element, nickel, aluminum, copper or a combination thereof is preferable. When the conductor coating 9 contains nickel, aluminum, copper or a combination thereof as a metal element, the conductivity of the conductor 3 can be further improved.
[0048] The mass per unit area of chromium contained in the chromium hydroxide on the outermost surface of the conductor coating 9 [mg / m 2 ] relative to the mass per unit area of chromium contained in trivalent chromium compounds [mg / m 2 ] is 0.30, preferably 0.40. When the mass ratio is less than 0.30, the conductor coating 9 cannot form a sufficient amount of hydrogen bonds with the maleic anhydride-modified polypropylene in the innermost layer 6, and the bonding strength between the conductor and the insulating film may become insufficient. The upper limit of the mass ratio of the chromium hydroxide to the chromium atoms per unit area of the trivalent chromium compound is 0.90, preferably 0.80. When the mass ratio exceeds 0.90, the mechanical strength of the conductor coating 9 is reduced, and the bonding strength between the conductor 3 and the insulating film 5 may become insufficient.
[0049] The conductor coating 9 preferably further contains a calcium compound, a fluorine compound or a combination thereof. By making the conductor coating 9 further contain a calcium compound, when the lead wire 1 for a non-aqueous electrolyte battery is used for a non-aqueous electrolyte battery, the stability of the conductor coating 9 to the decomposition products of the non-aqueous electrolyte components in the non-aqueous electrolyte battery is improved, so that it can have excellent corrosion resistance. By making the conductor coating 9 further contain a fluorine compound, the formation of a stable passivation film can be promoted, so the corrosion resistance can be further improved. As calcium compounds, for example, calcium oxide, calcium hydroxide, calcium carbonate, calcium chromate, calcium chromate dihydrate, anhydrous calcium chromate, calcium / aluminate compounds, etc. can be listed. As fluorine compounds, for example, calcium fluoride, chromium fluoride, aluminum fluoride, copper fluoride, etc. can be listed. The calcium compound and fluorine compound in the conductor coating 9 can be confirmed by XPS.
[0050] The lower limit of the average thickness of the conductor coating 9 is preferably 1 nm, more preferably 3 nm. By setting the average thickness of the conductor coating 9 to be 1 nm or more, sufficient corrosion resistance of the conductor 3 can be obtained. On the other hand, the upper limit of the average thickness of the conductor coating 9 is preferably 50 nm, more preferably 20 nm. By setting the average thickness of the conductor coating 9 to be 50 nm or less, the density reduction caused by the formation of cracks in the conductor coating 9 can be suppressed, and the corrosion resistance can be better maintained. The average thickness of the conductor coating 9 can be measured by analyzing the elements present on the surface of the conductor 3 covered by the conductor coating 9 using XPS.
[0051] (Insulating film)
[0052] The insulating film 5 is used as an insulating film of the non-aqueous electrolyte battery lead 1. The insulating film 5 has one or more insulating layers, and is laminated on the outer peripheral surface of the conductor 3 so as to cover at least a portion of the outer peripheral surface of the conductor 3. By making the insulating film 5 have one or more insulating layers 3, various functions can be imparted according to the purpose of the non-aqueous electrolyte battery lead 1. The non-aqueous electrolyte battery lead 1 of this embodiment includes an insulating film 5 having three insulating layers 3.
[0053] The lower limit of the average thickness of the insulating film 5 is preferably 0.05 mm. By making the average thickness of the insulating film 5 greater than 0.05 mm, the gap between the insulating film 5 and the packaging container 11 caused by the height difference of the thickness portion of the conductor 3 can be filled by the insulating film 5, thereby reliably sealing. In addition, as the lower limit of the average thickness of the insulating film 5, it can be further 0.08 mm or 0.10 mm. On the other hand, as the upper limit of the average thickness of the insulating film 5, it is preferably 0.50 mm. By making the average thickness of the insulating film 5 less than 0.50 mm, the amount of water that penetrates from the atmosphere through the insulating film 5 and penetrates into the non-aqueous electrolyte battery 10 can be reduced, thereby suppressing the deterioration of the non-aqueous electrolyte battery. In addition, as the upper limit of the average thickness of the insulating film 5, it can be further 0.40 mm or 0.30 mm. Here, in the present disclosure, the average thickness of the insulating film 5 is the average value of the thickness measurement values at 10 points on the surface with the largest area among the outer peripheral surface of the insulating film 5.
[0054] In the present embodiment, the insulating film 5 includes an innermost layer 6 laminated on the surface of the conductor 3 , a first insulating layer 8 laminated on the outermost surface of the insulating film 5 , and a second insulating layer 7 laminated on the inner surface of the first insulating layer 8 .
[0055] (Innermost layer)
[0056] The innermost layer 6 is laminated on the surface of the conductor coating 9. Since the insulating film 5 has the innermost layer 6, corrosion of the conductor 3 can be suppressed.
[0057] The innermost layer 6 has a resin component containing maleic anhydride-modified polypropylene (maleic anhydride-modified PP) as a main component. When the innermost layer 6 has a resin component containing maleic anhydride-modified polypropylene as a main component, the adhesion with the conductor coating 9 is improved.
[0058] The lower limit of the acid modification rate of the resin component is 0.02 mass %, preferably 0.10 mass %. By making the acid modification rate of the resin component 0.02 mass % or more, the adhesion between the innermost layer 6 and the conductor coating 9 can be improved, and sufficient tolerance to the non-aqueous electrolyte can be obtained. On the other hand, the upper limit of the acid modification rate of the resin component is 0.50 mass %, preferably 0.40 mass %. By making the acid modification rate of the resin component 0.50 mass % or less, the corrosion of the conductor 3 by the maleic anhydride modified group can be suppressed, and the corrosion resistance becomes good.
[0059] The acid modification rate was determined by infrared spectroscopy (FT-IR) based on the concentration of 1710 cm -1 The mass of the carboxyl group was measured by the peak area and calculated from the average thickness of the innermost 6 layers based on an appropriate calibration curve.
[0060] The melting point of the maleic anhydride-modified polypropylene is preferably 130° C. to 170° C., and more preferably 130° C. to 150° C. If the melting point of the maleic anhydride-modified polypropylene is less than 130° C., the heat resistance may be reduced. On the other hand, if the melting point of the maleic anhydride-modified polypropylene exceeds 170° C., the heat required to melt the maleic anhydride-modified polypropylene is large, so the maleic anhydride-modified polypropylene cannot be sufficiently melted, and sufficient adhesion of the innermost layer 6 to the conductor 3 may not be obtained.
[0061] The lower limit of the content of the maleic anhydride-modified polypropylene in the innermost layer 6 is preferably 0.1 mass %, more preferably 0.5 mass %. When the content of the maleic anhydride-modified polypropylene is less than 0.1 mass %, sufficient material properties for practical use may not be obtained.
[0062] In the innermost layer 6, the resin component may also contain a thermoplastic resin other than maleic anhydride-modified polypropylene within the range that does not hinder the effect of the present disclosure. As thermoplastic resins other than maleic anhydride-modified polypropylene, for example, polyolefins such as polypropylene and polyethylene can be cited. In addition, the innermost layer 6 may also contain other well-known additives. As well-known additives, for example, antioxidants, flame retardants, tackifiers, lubricants, fillers, crystallization accelerators, colorants, etc. can be cited.
[0063] As the lower limit of the average thickness of the innermost layer 6, 0.01mm is preferred. By making the average thickness of the innermost layer 6 above 0.01mm, sufficient adhesion to the conductor 3 can be obtained. In addition, as the lower limit of the average thickness of the innermost layer 6, it can be 0.02mm or 0.03mm. On the other hand, as the upper limit of the average thickness of the innermost layer 6, it is preferably 0.25mm. By making the average thickness of the innermost layer 6 below 0.25mm, the amount of water that penetrates from the atmosphere through the insulating film 5 into the non-aqueous electrolyte battery can be reduced, thereby suppressing the degradation of the battery. In addition, as the upper limit of the average thickness of the innermost layer 6, it can be 0.22mm or 0.20mm. Here, in the present disclosure, the average thickness of the innermost layer 6 is the average value of the thickness measurement values at 10 points on the surface with the largest area among the outer peripheral surface of the innermost layer 6.
[0064] (1st insulation layer)
[0065] The first insulating layer 8 is arranged farthest from the conductor 3 and is formed of a thermoplastic resin. The first insulating layer 8 is laminated on the outermost surface of the insulating film 5 and on the surface of the second insulating layer 7. The first insulating layer 8 preferably has as its main component a resin that is easily melted at a heat sealing temperature when the opening of the packaging container is heat-sealed (heat-sealed), and more preferably has as its main component a polyolefin.
[0066] As polyolefin, polypropylene, polyethylene, their derivatives, etc. can be cited. More specifically, a combination of homopolypropylene, block polypropylene, random polypropylene, low crystalline polypropylene, low density polyethylene, linear low density polyethylene, low crystalline ethylene-propylene copolymer, low crystalline ethylene-butene copolymer, low crystalline ethylene-octene copolymer, low crystalline propylene-ethylene copolymer, etc. can be cited. The first insulating layer 8 can also contain a variety of resins. As polyolefin, polypropylene is preferably used, and as polyolefin, random polypropylene having a melting point of 120°C to 155°C and an MFR of 3g / 10min to 15g / 10min is more preferably used. By making the polyolefin a random polypropylene, it has the advantage of being able to fully exert the adhesion with the second insulating layer 7 and the innermost resin layer of the packaging container.
[0067] The lower limit of the content of the polyolefin in the first insulating layer 8 is preferably 70% by mass. If the content of the polyolefin is less than 70% by mass, sufficient material properties may not be obtained for practical use. In addition, the lower limit of the content of the polyolefin in the first insulating layer 8 may be further 80% by mass, 90% by mass, or 100% by mass.
[0068] The first insulating layer 8 may contain a thermoplastic resin other than the above-mentioned polyolefin within a range not hindering the effects of the present disclosure.
[0069] The first insulating layer 8 may contain other known additives within the range not hindering the effects of the present disclosure. Examples of known additives include antioxidants, flame retardants, tackifiers, lubricants, fillers, crystallization accelerators, and colorants.
[0070] The lower limit of the average thickness of the first insulating layer 8 is preferably 25 μm. When the average thickness of the first insulating layer 8 is less than 25 μm, the strength of the first insulating layer 8 may not be fully obtained. In addition, the lower limit of the average thickness of the first insulating layer 8 may be further 30 μm or 40 μm. On the other hand, the upper limit of the average thickness of the first insulating layer 8 is preferably 250 μm. When the average thickness of the first insulating layer 8 exceeds 250 μm, the amount of moisture that penetrates from the atmosphere through the insulating film 5 into the non-aqueous electrolyte battery increases, which may accelerate the deterioration of the battery. Here, in the present disclosure, the average thickness of the first insulating layer 8 is the average value of the thickness measurement values at 10 points on the surface with the largest area among the outer peripheral surface of the first insulating layer 8.
[0071] (Second insulation layer)
[0072] The insulating film 5 may include a second insulating layer 7 between the first insulating layer 8 and the innermost layer 6. The second insulating layer 7 is laminated on the inner surface of the first insulating layer 8. The second insulating layer 7 preferably contains a cross-linked polyolefin or a polyolefin having a higher melting point than the innermost layer 6. By making the second insulating layer 7 contain a cross-linked polyolefin or a polyolefin resin having a higher melting point than the innermost layer 6, it is difficult to melt at the heat sealing temperature when the opening of the packaging container is heat-sealed, and the short circuit between the metal layer of the packaging container and the conductor can be suppressed.
[0073] Examples of the polyolefin in the cross-linked polyolefin include polypropylene, polyethylene, and derivatives thereof.
[0074] As the high melting point polyolefin, a high melting point polypropylene having a melting point of 155° C. or higher is preferred, and homopolypropylene, block polypropylene, thermoplastic olefin elastomer (TPO) and the like are particularly preferred.
[0075] The second insulating layer 7 may contain a thermoplastic resin other than the cross-linked polyolefin, or other known additives, within the scope of not hindering the effects of the present disclosure. Examples of known additives include antioxidants, flame retardants, tackifiers, lubricants, fillers, crystallization accelerators, and colorants.
[0076] The lower limit of the average thickness of the second insulating layer 7 is preferably 25 μm. When the average thickness of the second insulating layer 7 is less than 25 μm, the strength of the second insulating layer 7 may not be fully obtained. In addition, the lower limit of the average thickness of the second insulating layer 7 may be further 30 μm or 40 μm. On the other hand, the upper limit of the average thickness of the second insulating layer 7 is preferably 250 μm. When the average thickness of the second insulating layer 7 exceeds 250 μm, the amount of moisture that penetrates from the atmosphere through the insulating film 5 and penetrates into the non-aqueous electrolyte battery may easily increase. Here, in the present disclosure, the average thickness of the second insulating layer 7 is the average value of the thickness measurement values at 10 points on the surface with the largest area among the outer peripheral surface of the second insulating layer 7.
[0077] [Method for producing a lead wire for a non-aqueous electrolyte battery]
[0078] The method for producing the nonaqueous electrolyte battery lead is not particularly limited, and the lead can be produced by a known method.
[0079] First, at least a portion of the surface of the conductor is subjected to a chemical conversion treatment (chromate treatment) using a treatment liquid by the following method so as to cover the conductor coating.
[0080] First, for example, the surface, back and side of the conductor are degreased. When the conductor is formed, oily components may be attached to the surface, and the above degreasing is performed to remove these oily components or oil. The degreasing treatment can be performed by coating or immersing in an organic solvent, a surfactant, an acid or an alkali solution. Then, after washing, removing the organic solvent, surfactant, acid, and alkali solution, and drying, the metal surface is chemically converted using a liquid containing chromate as a main component.
[0081] Examples of the acidic compound used for degreasing include inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, and sulfamic acid; citric acid, gluconic acid, oxalic acid, tartaric acid, formic acid, glycolic acid, EDTA (ethylenediamine tetraacetic acid), and ammonium thioglycolate. In addition, as alkaline compounds, there can be listed sodium salts such as sodium hydroxide (NaOH), sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), Glauber's salt (Na2SO4·10H2O), sodium sesquicarbonate (Na2CO3·NaHCO3·2H2O); silicates such as sodium orthosilicate (2Na2O·SiO2, water content 10% to 40%), sodium metasilicate (2Na2O·SiO2·9H2O); phosphates such as sodium dihydrogen phosphate (NaH2PO4), sodium pyrophosphate (Na4P2O7), disodium hydrogen phosphate (Na2HPO4), sodium hexametaphosphate {(NaPO3)6}, sodium phosphate (Na3PO4), etc.
[0082] As a method of chemical conversion treatment, a method of immersing the conductor in a treatment liquid, a method of spraying the treatment liquid onto the conductor, a method of applying the treatment liquid to the conductor by a roll coating method, etc., is used, and the treatment liquid is applied to the conductor and dried, thereby chemical conversion treatment is performed on the surface, back surface, side surface, etc. of the conductor. In the chemical conversion treatment, at least the covering portion of the insulating film may be treated, but it is preferred to treat the entire circumference of the conductor by a dipping method, a spraying method, a roll coating method, etc.
[0083] As the treatment liquid for chemical conversion treatment, an aqueous solution containing 5.0 g / L of chromium chloride hexahydrate and 170 g / L of potassium formate was used. 2 The treatment solution is applied to the conductor by cathode electrolysis for 30 seconds under the conditions of , and then, after drying, baked at a heating temperature of 100° C. to 300° C. to form a conductor coating.
[0084] Next, an insulating film is covered on at least a portion of the outer circumference of the conductor covered by the conductor coating. There is no particular limitation on the method for manufacturing the insulating film. For example, a known mixing device such as an open-width roller, a pressure kneader, a single-shaft mixer, a double-shaft mixer, etc. is used to mix a forming resin composition containing the resin components and additives of each insulating layer. Next, when making each insulating layer, each film-like insulating layer can be made by extrusion molding such as T-die molding and inflation molding. Then, the insulating layers are overlapped and thermally laminated using a hot roller to paste them. In addition, a plurality of insulating layers can be formed simultaneously using a co-extrusion inflation method or a T-die method. In addition, an extrusion lamination method of laminating a molten resin on a film formed as a single layer can be used. The film-like insulating film is cut into a specified size and heated and pressurized from both sides of the conductor by a hot pressing method, thereby covering at least a portion of the outer circumference of the conductor.
[0085] In addition, the insulating layer can be produced by injection molding as well as extrusion molding. In injection molding, if resin is injected after the conductor is installed in the mold, the circumference of the conductor can be covered, and in the case of forming multiple layers, two-color molding can be used.
[0086] The lead wire for a non-aqueous electrolyte battery has excellent resistance to a non-aqueous electrolyte of the non-aqueous electrolyte battery.
[0087] <Non-aqueous electrolyte battery>
[0088] The non-aqueous electrolyte battery 10 includes the non-aqueous electrolyte battery lead 1 and a non-aqueous electrolyte. Examples of the non-aqueous electrolyte battery include secondary batteries such as lithium ion batteries.
[0089] Figure 3 1 is a perspective view showing an example of a non-aqueous electrolyte battery having a lead for the non-aqueous electrolyte battery. Figure 4 It is a partial cross-sectional view schematically showing one embodiment of a non-aqueous electrolyte battery. Figure 3 and Figure 4The non-aqueous electrolyte battery (non-aqueous electrolyte secondary battery) 10 shown has: a plate-shaped positive electrode, a plate-shaped negative electrode and a non-aqueous electrolyte (not shown); a packaging container 11; and a plurality of (specifically, two) non-aqueous electrolyte battery leads 1. The non-aqueous electrolyte battery lead 1 is the non-aqueous electrolyte battery lead described above. As described above, the insulating film 5 of the non-aqueous electrolyte battery lead 1 of the present embodiment has an innermost layer 6, a second insulating layer 7 and a first insulating layer 8. The non-aqueous electrolyte battery 10 has a substantially square packaging container 11 and two non-aqueous electrolyte battery leads 1 extending from the inside of the packaging container 11 to the outside. The conductor 3 and the packaging container 11 are connected together by the sealing portion 13 of the packaging container 11 through the insulating film 5. The packaging container 11 is a container that contains the positive electrode, the negative electrode, the separator and the non-aqueous electrolyte in a sealed state.
[0090] The positive electrode and the negative electrode (not shown) are stacked with a separator to form a stacked electrode group. The stacked electrode group and the non-aqueous electrolyte are contained in a sealed state in a packaging container 11. In the packaging container 11, the stacked electrode group is immersed in the electrolyte. As described later, the packaging container 11 is formed of a sheet body. In the packaging container 11, a sealing portion 13 around two sheets or one bent sheet body is sealed by heat welding.
[0091] like Figure 4 As shown, among the two non-aqueous electrolyte battery leads 1, one non-aqueous electrolyte battery lead 1 is arranged such that one end 4a of the conductor 3 is exposed from the outer container 11 and the other end 4b is connected to the positive electrode in the outer container 11. The other non-aqueous electrolyte battery lead 1 is arranged such that one end 4a of the conductor 3 is exposed from the outer container 11 and the other end 4b is connected to the negative electrode in the outer container 11.
[0092] The packaging container 11 is not stacked on both end portions of the conductor 3, namely, one end portion 4a and the other end portion 4b. One end portion 4a of the conductor 3 is exposed from the packaging container 11. On the other hand, the other end portion 4b of the conductor 3 of the non-aqueous electrolyte battery lead 1 on the positive electrode side is connected to the internal connection lead 14 via the welding portion 15, and is connected to the positive electrode (not shown) through the internal connection lead 14. In addition, the other end portion 4b of the conductor 3 of the non-aqueous electrolyte battery lead 1 on the negative electrode side is similarly connected to the internal connection lead 14 via the welding portion 15, and is connected to the negative electrode (not shown) through the internal connection lead 14. Figure 4 As shown, the middle portion of these nonaqueous electrolyte battery leads 1 is sandwiched by a sheet body serving as a packaging container 11 via an insulating film 5 , and in this portion, the packaging container 11 and the first insulating layer 8 of the plurality of nonaqueous electrolyte battery leads 1 are thermally welded.
[0093] The positive electrode and the negative electrode are typically a laminated body in which an active material layer containing an active material is laminated on the surface of a current collector such as a metal foil. The positive electrode and the negative electrode are usually in a plate shape, but may be in a shape other than a plate shape.
[0094] The separator is generally an insulating and porous film and is impregnated with a non-aqueous electrolyte.
[0095] The nonaqueous electrolyte solution contains a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.
[0096] like Figure 4 As shown in FIG. 1 , the packaging container 11 is composed of a sheet body in which an innermost resin layer 27, a metal layer 25, and an outermost resin layer 26 are sequentially stacked. The packaging container 11 is formed by stacking two sheets and heat-sealing three sides except for the side through which the conductor passes, thereby forming a sealed portion 13. In addition, in the sealed portion 13, the conductor 3 of each non-aqueous electrolyte battery lead 1 is bonded to the packaging container 11 via an insulating film 5. In this portion, the innermost resin layer 27 of the packaging container 11 and the first insulating layer 8 of each non-aqueous electrolyte battery lead 1 are heat-fused.
[0097] The innermost resin layer 27 is directly laminated on the inner surface of the metal layer 25. The innermost resin layer 27 located inside the packaging container 11 is preferably made of an insulating resin that is insoluble in the non-aqueous electrolyte and melts when heated. As the innermost resin layer 27, for example, polyolefin, acid-modified polyolefin, acid-modified styrene elastomer, etc. can be used. As the innermost resin layer 27, polypropylene is preferred among these. In addition, as the range of the average thickness of the innermost resin layer 27, it is preferably about 10 μm or more and 500 μm or less.
[0098] The metal layer 25 has the function of improving the strength of the packaging container 11 and preventing water vapor, oxygen, light, etc. from penetrating into the battery. The metal layer 25 is formed of a metal such as aluminum foil. The metal layer 25 has a metal as a main component. Examples of the metal include aluminum, copper, stainless steel, titanium, etc., with aluminum being particularly preferred. The metal layer 25 is substantially formed of a metal, but may also contain additives other than metals. The metal layer 25 is film-shaped, preferably formed of a metal foil, more preferably formed of an aluminum alloy foil. In addition, the average thickness of the metal layer 25 is preferably about 10 μm or more and about 50 μm or less.
[0099] The outermost resin layer 26 has the function of protecting the outer surface of the metal layer 25 and the function of insulation. As the outermost resin layer 26 located on the outside of the packaging container, the insulating material usually uses resin as the main component. As the resin forming the outermost resin layer 26, for example, polyethylene terephthalate (PET), polyamide, polyester, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin, polyetherimide, polyimide, and mixtures or copolymers thereof can be listed. The outermost resin layer 26 can also be composed of multiple layers, for example, via an adhesive layer containing polyethylene terephthalate, polyamide, etc. In addition, the average thickness of the outermost resin layer 26 is preferably in the range of about 10 μm to 50 μm.
[0100] In the non-aqueous electrolyte battery 10, as described above, one end of the non-aqueous electrolyte battery lead 1, i.e., one end portion 4a of the conductor 3, is arranged in a state of being exposed from the packaging container 11 and sealed by the packaging container 11. Specifically, the non-aqueous electrolyte battery lead 1 is arranged so that the innermost resin layer of the packaging container 11 is in direct contact with the insulating film 5 of the non-aqueous electrolyte battery lead 1. In addition, in the state where the non-aqueous electrolyte battery lead 1 is arranged in this way, the innermost resin layer 27 in the sealing portion 13 of the packaging container 11 is thermally welded to the first insulating layer 8 of the non-aqueous electrolyte battery lead 1. As a result, the stacked electrode group immersed in the non-aqueous electrolyte, i.e., the positive electrode, the negative electrode, and the separator can be sealed in the packaging container 11.
[0101] [Method for manufacturing non-aqueous electrolyte battery]
[0102] The method for manufacturing a non-aqueous electrolyte battery according to one embodiment of the present disclosure can be appropriately selected from known methods. The method for manufacturing a non-aqueous electrolyte battery includes, for example, a step of preparing a lead for the non-aqueous electrolyte battery; a step of preparing a stacked electrode group; a step of preparing a non-aqueous electrolyte; and a step of accommodating the stacked electrode group connected with the lead for the non-aqueous electrolyte battery and the non-aqueous electrolyte in a packaging container.
[0103] By providing the nonaqueous electrolyte battery with a plurality of the nonaqueous electrolyte battery leads, it is possible to suppress separation of the conductor and the insulating film, thereby improving sealing properties.
[0104] [Other embodiments]
[0105] The embodiments disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present disclosure is not limited to the configuration of the above embodiments, but is indicated by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims.
[0106] In the above embodiment, the non-aqueous electrolyte battery lead has an insulating film having a three-layer structure including an innermost layer, a second insulating layer, and a first insulating layer, but the non-aqueous electrolyte battery lead may also have an insulating film having a two-layer structure not including the second insulating layer. In addition, the non-aqueous electrolyte battery lead may also have an insulating film having a multi-layer structure having one or more intermediate layers inside the second insulating layer.
[0107] Example
[0108] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the following examples.
[0109] [Test No. 1]
[0110] (Production of lead conductors)
[0111] As the substrate of the lead conductor, an oxygen-free copper plate (C1020) with a length of 100 mm, a width of 45 mm, and an average thickness of 0.2 mm was used. As a pretreatment, the substrate was immersed in a sodium hydroxide aqueous solution (40 g / L) at 25°C and at 1.0 A / dm 2 The degreased substrate is cleaned with running water.
[0112] Next, the washed substrate was immersed in a 10 mass % sulfuric acid aqueous solution at 25° C. for 30 seconds to perform acidification. The acidified substrate was washed with running water.
[0113] Next, nickel amide sulfate tetrahydrate (350 g / L), nickel chloride hexahydrate (30 g / L) and boric acid (30 g / L) were mixed to obtain a nickel plating solution. The acidified substrate was immersed in the nickel plating solution at 50°C and charged at 5.0 A / dm 2 The plating was performed for 120 seconds at a current density of . The plated substrate was washed with running water to obtain a lead conductor made of nickel-plated copper (metal plated with nickel).
[0114] (Formation of Conductor Coating)
[0115] Chromium chloride hexahydrate (5.0 g / L) and potassium formate (170 g / L) were mixed in pure water to obtain a surface treatment solution. The lead conductor was immersed in the surface treatment solution at 45°C and heated at 10 A / dm 2 The cathode electrolysis was carried out for 30 seconds at a current density of 1.50 ℃. The lead conductor after the cathode electrolysis was washed with running water and dried in a constant temperature bath at 100° C. for 180 seconds to obtain a lead conductor with a conductor coating. On the outermost surface of the conductor coating, the mass per unit area of chromium contained in the chromium hydroxide [mg / m 2 ] relative to the mass per unit area of chromium contained in the above trivalent chromium compound [mg / m2 ] is 0.40.
[0116] (Production of insulating film)
[0117] A two-layer insulating film including an innermost layer and a first insulating layer was produced. First, resin compositions for the innermost layer and the first insulating layer were produced using a mixing device.
[0118] (1) Innermost layer
[0119] 100 parts by mass of "PRIME POLYPRO F227D" (melting point 142°C, MFR 7) manufactured by Prime Polypropylene Co., Ltd. as random polypropylene (random PP) and 1 part by mass of "POLYBOND 3000" (melting point 157°C, acid modification rate 1.2% by mass) manufactured by SII group as maleic anhydride-modified polypropylene were kneaded using a biaxial kneader to obtain a resin component having an acid modification rate of 0.01% by mass.
[0120] (2) First insulation layer
[0121] As a material of the resin composition of the first insulating layer, random polypropylene: "PRIME POLYPRO F227D" manufactured by Prime Polypropylene Co., Ltd. (MFR 7 g / 10 min, melting point 140° C.) was used.
[0122] (3) Fabrication of insulating film
[0123] Next, by using two double-layer T-die film-forming machines of a coating hanger type equipped with two single-screw extruders, the innermost layer resin composition was put into the first extruder, and the first insulating layer resin composition was put into the second extruder, and co-extruded to obtain a two-layer insulating film in which the innermost layer resin composition / the first insulating layer resin composition were sequentially laminated. The average thickness of the innermost layer was 50 μm, and the average thickness of the first insulating layer was 100 μm.
[0124] (Manufacturing of Lead Wires for Non-aqueous Electrolyte Batteries)
[0125] Next, the obtained two-layer insulating film was cut into a predetermined size, and both surfaces of the conductor were heat-sealed under the conditions of a mold temperature of 220° C. and a surface pressure of 0.2 MPa. Thus, a No. 1 non-aqueous electrolyte battery lead was obtained.
[0126] [Test No.2]
[0127] In the preparation of the insulating film, as the material of the innermost layer resin composition, 100 parts by mass of "PRIME POLYPRO F227D" manufactured by Prime Polypropylene Co., Ltd. as a random polypropylene and 5 parts by mass of "POLYBOND3000" manufactured by SIIgroup as a maleic anhydride-modified polypropylene were used to obtain a resin component with an acid modification rate of 0.06% by mass. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as in Test No. 1.
[0128] [Test No.3]
[0129] In the preparation of the insulating film, as the material of the innermost layer resin composition, 100 parts by mass of "PRIME POLYPRO F227D" manufactured by Prime Polypropylene Co., Ltd. as a random polypropylene and 15 parts by mass of "POLYBOND 3000" manufactured by SII group as a maleic anhydride-modified polypropylene were used to obtain a random PP with an acid modification rate of 0.18% by mass. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as in Test No. 1.
[0130] [Test No.4]
[0131] In the preparation of the insulating film, as the material of the innermost layer resin composition, 100 parts by mass of "PRIME POLYPRO F227D" manufactured by Prime Polypropylene Co., Ltd. as a random polypropylene and 40 parts by mass of "POLYBOND 3000" manufactured by SII group as a maleic anhydride-modified polypropylene were used to obtain a random PP with an acid modification rate of 0.48% by mass. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as in Test No. 1.
[0132] [Test No.5]
[0133] In the preparation of the insulating film, as the material of the innermost layer resin composition, 100 parts by mass of "PRIME POLYPRO F227D" manufactured by Prime Polypropylene Co., Ltd. as a random polypropylene and 50 parts by mass of "POLYBOND3000" manufactured by SIIgroup as a maleic anhydride-modified polypropylene were used to obtain a random PP with an acid modification rate of 0.60% by mass. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as in Test No. 1.
[0134] [Test No.6]
[0135] In the formation of the conductor coating, the lead conductor after cathode electrolysis was washed with running water and dried in a constant temperature bath at 100°C for 30 seconds to obtain a lead conductor with a conductor coating. On the outermost surface of the conductor coating, the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound was 0.80. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as No. 3.
[0136] [Test No.7]
[0137] In the formation of the conductor coating, the lead conductor after cathode electrolysis was washed with running water and dried in a constant temperature bath at 80°C for 20 seconds to obtain a lead conductor with a conductor coating. On the outermost surface of the conductor coating, the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound was 0.95. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as No. 3.
[0138] [Test No.8]
[0139] In the formation of the conductor coating, the lead conductor after cathode electrolysis was washed with running water and dried in a constant temperature bath at 250°C for 3600 seconds to obtain a lead conductor with a conductor coating. On the outermost surface of the conductor coating, the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound was 0.20. Except for this, a lead for a non-aqueous electrolyte battery was obtained in the same manner as No. 3.
[0140] [Test No.9]
[0141] As the base material of the lead conductor, a flat conductor made of an aluminum plate with a length of 100 mm, a width of 45 mm, and an average thickness of 0.4 mm was used. Then, in the formation of the conductor coating, chromium chloride hexahydrate (5.0 g / L) and potassium formate (170 g / L) were mixed in pure water to obtain a surface treatment solution. The lead conductor was immersed in the surface treatment solution at 45°C and heated at 10 A / dm 2 The cathode electrolysis was carried out for 10 seconds at a current density of 1.50 Å. The lead conductor after the cathode electrolysis was washed with running water to obtain a lead conductor having a conductor coating, wherein the ratio of the mass per unit area of chromium contained in the chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound on the outermost surface of the conductor coating was 0.60. A lead for a non-aqueous electrolyte battery was obtained in the same manner as in No. 3 except that the ratio was 0.60.
[0142] [Test No.10]
[0143] As the base material of the lead conductor, a flat conductor made of an aluminum plate with a length of 100 mm, a width of 45 mm, and an average thickness of 0.4 mm was used. In the formation of the conductor coating, chromium chloride hexahydrate (5.0 g / L), potassium formate (170 g / L), and potassium fluoride (5.0 g / L) were mixed in pure water to obtain a surface treatment solution. The lead conductor was immersed in the surface treatment solution at 45°C and heated at 10 A / dm 2 The cathode electrolysis was carried out for 10 seconds at a current density of 1.50 ℃. The lead conductor after the cathode electrolysis was washed with running water to obtain a lead conductor having a conductor coating, wherein the ratio of the mass per unit area of chromium contained in the chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound on the outermost surface of the conductor coating was 0.40. A lead for a non-aqueous electrolyte battery was obtained in the same manner as in No. 3 except that the ratio was 0.40.
[0144] [Test No.11]
[0145] In forming the conductor coating, chromium chloride hexahydrate (5.0 g / L), potassium formate (170 g / L) and calcium chloride (0.5 g / L) were mixed in pure water to obtain a surface treatment solution. The lead conductor was immersed in the surface treatment solution at 45°C and heated at 10 A / dm 2 The cathode electrolysis was carried out for 30 seconds at a current density of . The lead conductor after the cathode electrolysis was washed with running water and dried in a constant temperature bath at 100° C. for 180 seconds to obtain a lead conductor having a conductor coating, wherein the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound on the outermost surface of the conductor coating was 0.50. A lead for a non-aqueous electrolyte battery was obtained in the same manner as in No. 2 except that the ratio was 0.50.
[0146] [Test No.12]
[0147] In forming the conductor coating, chromium chloride hexahydrate (5.0 g / L), potassium formate (170 g / L) and calcium chloride (5.0 g / L) were mixed in pure water to obtain a surface treatment solution. The lead conductor was immersed in the surface treatment solution at 45°C and heated at 10 A / dm 2 The cathode electrolysis was carried out for 30 seconds at a current density of . The lead conductor after the cathode electrolysis was washed with running water and dried in a constant temperature bath at 100° C. for 180 seconds to obtain a lead conductor having a conductor coating, wherein the ratio of the mass per unit area of chromium contained in the chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound on the outermost surface of the conductor coating was 0.20. A lead for a non-aqueous electrolyte battery was obtained in the same manner as in No. 2 except that the ratio was 0.20.
[0148] [Test No.13]
[0149] As the base material for the lead conductor, an oxygen-free copper plate (C1020) with a length of 100 mm, a width of 45 mm, and an average thickness of 0.2 mm was used. As a pretreatment, the base material was immersed in an aqueous sodium hydroxide solution (40 g / L) at 25 °C and subjected to cathodic electrolytic degreasing at a current density of 1.0 A / dm 2 The degreased base material was washed with running water.
[0150] Next, for the washed base material, the base material was immersed in a sulfuric acid aqueous solution (10 mass%) at 25 °C for 30 seconds for acidification. The acidified base material was washed with running water. Next, without performing the step of using a nickel plating solution, a lead wire for a non-aqueous electrolyte battery was obtained in the same manner as in No. 3 except for this.
[0151] [Evaluation]
[0152] (Ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound)
[0153] The ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound in the outermost surface of the conductor coating film can be measured by using X-ray photoelectron spectroscopy (XPS: X-ray Photoelectron Spectroscopy). The measurement conditions of XPS are as follows. By performing curve fitting on the spectrum obtained according to the following measurement conditions, the ratio of the peak areas is obtained, and thereby the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound is calculated.
[0154] <Measurement Conditions of XPS>
[0155] X-ray source: Al-Kα
[0156] Output power of X-ray source: 15 kV
[0157] Photoelectron extraction angle: 45°
[0158] Analysis area: 100 μmφ
[0159] (Maleic anhydride modification rate of polypropylene)
[0160] The maleic anhydride modification rate of polypropylene is calculated by using "Nicolet8700" manufactured by Thermo Fisher Scientific, Inc., by infrared spectroscopic transmission method, based on the mass of carboxyl groups measured from the peak area at 1710 cm -1 and converted from the average thickness of the innermost layer based on an appropriate calibration curve.
[0161] (Evaluation of tolerance to non-aqueous electrolyte)
[0162] <Peeling test after immersion in electrolyte>
[0163] A peeling test after immersion in electrolyte was performed on Test No. 1 to Test No. 13. As an electrolyte, a test solution was prepared by mixing ethylene carbonate, diethyl carbonate, and dimethyl carbonate in a volume ratio of 1:1:1, and dissolving lithium hexafluorophosphate (LiPF6) in a manner to become 1.0 mol / L. After adjusting the water content of the electrolyte to 1000 ppm, the lead wires for the non-aqueous electrolyte batteries of Test No. 1 to Test No. 13 were immersed in the electrolyte and placed in a constant temperature bath at 80°C for 4 weeks. Then, the peeling test of Test No. 1 to Test No. 13 after immersion in the electrolyte was performed by the following method. One of the lead conductors and insulating films of Test No. 1 to Test No. 13 was cut and bent to 180°, and placed in a tensile testing machine ("EX-SX" manufactured by Shimadzu Corporation). The cut portion was stretched at a stretching speed of 50 mm / min to evaluate the presence or absence of peeling at the interface between the conductor and the insulating film.
[0164] [Table 1]
[0165]
[0166] As shown in Table 1, in the lead for the non-aqueous electrolyte battery, the conductor is covered with a conductor coating containing a trivalent chromium compound containing chromium hydroxide and a metal element, the innermost layer of the insulating film laminated on the surface of the conductor coating has a resin component containing maleic anhydride-modified polypropylene as a main component, and the acid modification rate of the above resin component is 0.02 mass % to 0.50 mass %. Test No. 2 to Test No. 4, Test No. 6, Test No. 9 to Test No. 11 and Test No. 13 did not peel off at the interface between the conductor and the insulating film in the peeling test, and had good tolerance to the non-aqueous electrolyte.
[0167] On the other hand, in Test No. 1 in which the acid modification rate of the resin component as the main component of the innermost layer was less than 0.02 mass %, in Test No. 5 in which the acid modification rate of the above resin component exceeded 0.50 mass %, in Test No. 7 in which the ratio of the mass per unit area of chromium contained in chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound in the outermost surface of the conductor coating exceeded 0.90, and in Tests No. 8 and No. 12 in which the ratio of the mass per unit area of chromium contained in the above chromium hydroxide to the mass per unit area of chromium contained in the trivalent chromium compound was less than 0.30, peeling was observed at the interface between the conductor and the insulating film in the peeling test, and the resistance to the non-aqueous electrolyte was poor.
[0168] The above results show that the lead for a non-aqueous electrolyte battery has excellent resistance to the non-aqueous electrolyte of the non-aqueous electrolyte battery.
[0169] Explanation of symbols
[0170] 1 Lead wire for non-aqueous electrolyte batteries
[0171] 3 Conductors
[0172] 4a One end
[0173] 4b The other end
[0174] 5 Insulation film
[0175] 6 Innermost layer
[0176] 7 Second insulation layer
[0177] 8 1st insulation layer
[0178] 9 Conductor coating
[0179] 10 Non-aqueous electrolyte battery
[0180] 11 Packaging Container
[0181] 13. Sealing part
[0182] 14 Internal connection leads
[0183] 15 Welding Department
[0184] 25 Metal Layer
[0185] 26 Outermost resin layer
[0186] 27 Innermost resin layer
Claims
1. A lead for a non-aqueous electrolyte battery, comprising: Conductors; and an insulating film having one or more layers and covering at least a portion of the outer peripheral surface of the conductor, The conductor has a conductor coating covering at least a portion of the surface. The conductor coating contains a trivalent chromium compound including chromium hydroxide and a metal element. The mass per unit area of chromium contained in the chromium hydroxide at the outermost surface of the conductor coating is mg / m 2 The mass per unit area of chromium contained in the trivalent chromium compound is mg / m 2 The ratio is 0.30 or more and 0.90 or less, The insulating film has an innermost layer, which is stacked on the surface of the conductor coating. The innermost layer has a resin component containing maleic anhydride-modified polypropylene as a main component, The acid modification rate of the resin component is 0.02 mass % or more and 0.50 mass % or less.
2. The lead for a non-aqueous electrolyte battery according to claim 1, wherein: The metal element is nickel, aluminum, copper or a combination thereof.
3. The lead for a non-aqueous electrolyte battery according to claim 1 or claim 2, wherein: The conductor coating further contains a calcium compound, a fluorine compound, or a combination thereof.
4. The lead for a non-aqueous electrolyte battery according to any one of claims 1 to 3, wherein: The acid modification rate of the resin component is 0.10 mass % or more and 0.50 mass % or less.
5. The lead for a non-aqueous electrolyte battery according to any one of claims 1 to 4, wherein: The average thickness of the conductor coating is not less than 1 nm and not more than 50 nm.
6. The lead for a non-aqueous electrolyte battery according to any one of claims 1 to 5, wherein: The average thickness of the insulating film is greater than or equal to 0.05 mm and less than or equal to 0.50 mm.
7. The lead for a non-aqueous electrolyte battery according to any one of claims 1 to 6, wherein: The average thickness of the innermost layer is not less than 0.01 mm and not more than 0.25 mm.
8. The lead for a non-aqueous electrolyte battery according to any one of claims 1 to 7, wherein: The conductor is nickel, nickel-plated metal, nickel-phosphorus alloy metal, aluminum or aluminum alloy.
9. A non-aqueous electrolyte battery comprising: Packaging container; A plurality of non-aqueous electrolyte battery leads according to any one of claims 1 to 8 arranged to extend from the inside to the outside of the packaging container; and Non-aqueous electrolyte.
Citation Information
Patent Citations
Non-aqueous electrolytic battery
JP1997265974A